A rare presentation of central granular cell odontogenic tumor - Koth, Valesca Sander (2021)
The central granular cell odontogenic tumor (CGCOT) is a rarely seen neoplasm of odontogenic origin with a predilection for mandible of middle aged women. The lesion shows slow growing and radiographic feature of a radiolucent unilocular lesion with a radiopaque border. The present study aims to report a new case of CGCOT with an atypical involvement of anterior maxilla. Clinical exam showed swelling of the hard palate and the vestibular area of left canine and pre-molar of maxilla. Cone beam computed tomography showed a hypodense unilocular well delimited lesion extending from central left incisive to left pre-molar region. Histopathological analysis showed granular eosinophilic cells and islands of odontogenic epithelium and positive immunostaining for CK14, vimentin, CD68, Ki67 and S-100, which established the diagnosis of CGCOT. The patient is under follow-up without recurrence for sixteen months.